Prolonging the shelf life of fresh-cut guava (Psidium guajaya L.) by coating with chitosan and cinnamon essential oil - Z.A., Nur Hanani; Soo, K. L.; W. I., Wan Zunairah; S., Radhiah (Elsevier, 2023)
This study investigated the effect of a coating of chitosan (CH) and cinnamon essential oil (CEO; 0− 1 %) on the quality attributes of fresh-cut guava (Psidium guajaya L.) during storage at 4 ± 1 ◦C for 17 days, with uncoated fresh-cut guava used as control. The CH coating significantly (p < 0.05) delayed changes in weight loss, firmness, colour, total soluble solids and titratable acidity compared to the control sample. Furthermore, the effects were more prominent with the incorporation of higher CEO concentrations. The bacterial, yeast and mould counts were also significantly lower (p < 0.05) in the CH-coated samples than in the control, with the coating containing 1 % CEO exhibiting the best quality preservation effect. In addition, CH and CEO coatings extended the shelf life of fresh-cut guava up to 17 days compared to the control sample (shelf life of only 3 days). In conclusion, combining CH and CEO as a coating matrix effectively preserves the quality and enhances fresh-cut guava’s shelf life.